MODERN LABORATORY DIAGNOSIS OF SEPSIS (International Conference on Modern Science and Scientific Studies, 2025)
Sepsis is now considered to be the result of an uncontrolled systemic inflammatory response (generalized inflammatory response) to the presence of infection [1,2,3].